FAST discovery of an extra plume in DDO 168. Issue 1 (22nd February 2023) - Yu, Nai-Ping; Zhu, Ming; Xu, Jin-Long; Zhang, Chuan-Peng; Liu, Xiao-Lan; Jiang, Peng; Wang, Jun-Jie
ABSTRACT: With the aim to study the extended H i environment around dwarf galaxies in the local universe, we performed a high-sensitivity H i observation of the DDO 168 and DDO 167 pair using the Five-hundred-meter Aperture Spherical Radio Telescope (FAST). We chose this pair as previous studies indicate that DDO 168 might have undergone an interaction with a local companion. Based on this deep observation, no new extra gas was found around DDO 167 and it was hardly resolved by FAST. On the other hand, on the north side of DDO 168 we discovered an extended plume of H i gas which has never been detected before. The plume has a ring-like structure with a radius of about 5.0 kpc and its gas mass is estimated to be 5.2 × 10 7 M⊙ . The expanding velocity of the plume is about 30 km s −1, corresponding to a dynamical age of about 200 Myr. The position–velocity (PV) diagrams cut through the two galaxies show a short and pronounced 'spur' pointing to DDO 167 from DDO 168, indicating a tidal interaction between the two galaxies. We also found an H i knot in the plume. The gas mass of the knot is about 9.5 × 10 6 M⊙ . This value is much higher than its virial mass, indicating the knot is gravitationally unstable and star formation will take place there in the future. Our study suggests that the ring-like structure of the plume might be caused by the passage of DDO 167 through the outer disc of DDO 168 about 200 Myr ago. We also discussed other plausible scenarios for the origin of the plume.